Developing A Web-Based Interactive Arabic Assessment To Stimulate Students’ Interest In Learning - Nurlaila, Nurlaila; Aisyah, Devy; Al Husna, Lathifah; Kamaluddin, Kamaluddin; Widayanti, Rizka; Asfar, Hadid; Anisa, Azkia (Ijaz Arabi Journal of Arabic Learning, 2025)
This research aims to produce a valid and practical web-based interactive Arabic assessment to stimulate students' interest in learning, especially students in Madrasah Aliyah. This type of research is Research & Development. This research was conducted through the feasibility and practicality stages. The research data were collected through questionnaires distributed to experts, teachers, and students, then processed through descriptive statistics. This research and development showed that the web-based interactive Arabic assessment developed to stimulate students' interest in learning at Madrasah Aliyah was categorised as very feasible, with an average score of 4.26, and also categorised as very practical, with an average score of 4.395. Based on the research and development results, it is hoped that teachers can use the developed web-based interactive Arabic assessment to stimulate students' interest in learning at Madrasah Aliyah.